Resistência à corrosão dos aços AISI 317L e SAF 2304 em meio de glicerina acidificada contendo cloretos obtida na produção de biodiesel - Fernanda de Lima Menezes (2015)
Biodiesel and glycerin, obtained from an ester and an alcohol in the presence of an acid or base catalyst, are produced by the transesterification reaction. The glycerin production process in a biodiesel industry undergoes a step neutralization of basic catalyst, sodium methylate, with hydrochloric acid. However, the glycerin obtained is acidified and chloride remains in the system, which is responsible for the pitting corrosion in points of production line. To prevent this kind of attack the austenitic and lean duplex stainless steels are used on the plant. The austenitic stainless steel has more nickel and molybdenum than the lean duplex. However, duplex stainless steel has more chromium and it combine the ferritic phase good mechanical properties with the austenite corrosion resistance. In the literature, reviews that approach the corrosion of acidified glycerin with chloride from a biodiesel industry in this type of stainless steels are very limited. Thus, the scope of this research is to study the pitting corrosion resistance of the AISI 317L, SAF 2304 cold rolling and SAF 2304 hot rolling in acidified glycerin with chloride solution at 337K. Potentiodynamic polarization in anodic direction was carry out in order to record the steels corrosion potential (Ecorr) and pitting potential (Epit). The materials corrosion behavior was then correlated with the surface layers microstructure and composition, using scanning electron microscope (SEM), energy dispersive spectroscopy (EDS) and atomic force microscope (AFM) characterization techniques. The analyzes showed that the steel AISI 317L was less resistant than the SAF 2304 in the studied conditions. Still, the corrosion resistance of lean duplex hot rolling was similar than the cold rolling in the analyzed solution and temperature.